1982
DOI: 10.1007/bf00428496
|View full text |Cite
|
Sign up to set email alerts
|

Histological changes during regression induced by retinoic acid in a transplantable rat chondrosarcoma

Abstract: Daily oral treatment with retinoic acid (100 mg/kg bodyweight) induced regression of a transplantable rat chondrosarcoma. In a previous biochemical investigation we have shown that the tissue breakdown is preceded by the loss of proteoglycan. The present study describes the histological changes induced by retinoic acid. A decrease in the intensity of metachromatic staining with toluidine blue was noted already after 1 day and the discoloration was almost complete after 4 days correlating with the loss of prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…These findings encourage us to study the effects and actions of the RARγ agonists to better understand the utility of this drug for the treatment of chondrosarcomas. Previous research on RA has demonstrated that oral administration of RA at 100 mg/kg for 7 days reduced the tumor size of rat chondrosarcoma cells that were subcutaneously transplanted in rats . This treatment reduced the metachromatic staining for proteoglycan, induced necrotic cells in the center part of the tumor mass, and increased collagen staining in Masson's trichrome staining.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…These findings encourage us to study the effects and actions of the RARγ agonists to better understand the utility of this drug for the treatment of chondrosarcomas. Previous research on RA has demonstrated that oral administration of RA at 100 mg/kg for 7 days reduced the tumor size of rat chondrosarcoma cells that were subcutaneously transplanted in rats . This treatment reduced the metachromatic staining for proteoglycan, induced necrotic cells in the center part of the tumor mass, and increased collagen staining in Masson's trichrome staining.…”
Section: Discussionmentioning
confidence: 83%
“…Retinoic acid (RA) has been known to alter chondrocyte growth and matrix production . Additionally, RA has been demonstrated previously to inhibit the growth of chondrosarcoma cells in vitro and in animal studies . These findings suggest the potential of RA as a therapeutic agent for skeletal disorders of cartilage, however, the use of this drug is not without side effects .…”
mentioning
confidence: 99%
“…Chondrosarcomas undergo growth inhibition after treatment with retinoic acids or selective agonists of RARγ (retinoic acid receptor gamma) in vitro and in vivo [39][40][41][42]. However, retinoic acid is not part of the standard chondrosarcoma treatment protocol, as it is in high-risk neuroblastoma treatment [37,39].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in order to test dependence or independence of the retinoic acid effects on DNA-synthesis, we incubated humeri in the presence of inhibitors of DNA synthesis to determine whether hydroxyurea (1-5 mM), cytosine arabinoside (10-100 pM), or bromodeoxyuridine (0.1-1.0 mM) affected the retinoic acid effects. None of the three inhibitors affected the retinoic effects (data not shown) indicating that the retinoic acid-induced changes occurred in a fixed population of cells and might implicate cell dedifferentiation [6].…”
Section: Independence Of Retinoic Acid Effects On Dna Synthesismentioning
confidence: 97%
“…of a generalized toxic effect. 4) Chondrosarcoma regression in response to retinoic acid involves a dynamic morphologic resorption pattern including chondroclast-like activity of monocytes and fibroblasts [6]. 5) Virtually the same structure-activity relationship, at least of retinoids with a carboxylic acid endgroup, was found in fetal bone cultures [15] as in other test systems [20] indicating that the biologic activity of retinoids in the various test systems may be based on the same underlying mechanisms of action.…”
Section: Discnssionmentioning
confidence: 99%